The Effectiveness Of Scraps-Made Realia For Teaching Speaking For The First Graders (An Experimental Study Conducted At SD 1 PEDES) - Puji Lestari, Antika Septiana; Setyawan, Agustinus Hary (LPPM Universitas Mercu Buana Yogyakarta, 2017)
There were many students that had problem in their speaking ability. Based on the problem, this research aims to: (1)Find out the result of students’ learning speaking by using scraps-made realia; (2) Find out the result of students’learning speaking without using scraps-made realia; (3) Define the students’ achievement in learning speaking byusing scraps-made realia. This research involved class 1A and class 1B of SD 1 Pedes which have 44 students for eachclass. The researcher used pre-test and post-test to analyze the students’ achievement in speaking skill. It was foundthat the mean of pre-test was 50 while the mean of post-test was 77,27. The obtained data of the t-test result was27,447. It means that t-test was higher than t-table (27,447 > 2,018). It means that the post-test was higher than pretest.In conclusion, the finding of this research showed that teaching speaking by using scraps-made realia waseffective to teach speaking skill. Hence, the researcher suggested to use scraps-made realia as alternative media inteaching speaking.